Predicting Success of Allergen-Specific Immunotherapy - Zissler, Ulrich M.; Schmidt-Weber, Carsten B. (Frontiers in Immunology, 2020)
The immune response to antigens is key aspect of immunology as it provides opportunities for therapeutic intervention. However, the induction of immunologic tolerance is an evolving area that is not sufficiently understood. Allergen immunotherapy (AIT) is a disease-modulating therapy available for IgE-mediated airway diseases such as allergic rhinitis, allergic asthma. This disease-modifying effect is not only antigen-driven, but also antigen-specific. The mechanism and, in consequence, therapy guiding biomarker are still at its infancy. Recent studies demonstrated that the interaction of T-, B-cells, macrophages and dendritic cells as well as epithelial cells are individually contributing to clinical tolerance and therefore underline the need for a multi-analyte system to monitor the progress and success of AIT. As clinical improvement is often accompanied by decreases in numbers of effector cells in tissue, analyses of cellular responses and cytokine pattern provide a good insight into the mechanisms of AIT. Suppression of type-2 immunity is accompanied by decreased levels of type-2 key mediators interleukin-4 and IL-13 or epithelial CCL-26, an increase of type-1 mediators like interferon-gamma, and IL-10+ B cells as well as tissue-homeostating factors like IDO expressed by macrophages and dendritic cells. It is not clear whether the altered long-term memory resides within the T-cell or the B-cell compartment. However, these analyses may not reveal useful or consistently reliable biomarkers in a clinical setting. Eventually, there is a strong need for more research to confirm and interpret possible associations with biomarkers and clinical response to AIT.